Mapping Atrial Fibrillation Drivers - Takahashi, Yoshihide (Reviews in cardiovascular medicine, 2024)
Understanding the initiating role of pulmonary veins in atrial fibrillation (AF) has led to the development of pulmonary vein isolation (PVI). The efficacy of PVI is high for paroxysmal AF, whereas it is limited for non-paroxysmal AF. This fact highlights the necessity of understanding the mechanism through which AF is maintained, to develop ablation strategies that would be required in addition to the PVI. Mapping AF in animal models and humans has led to the identification of focal or rotational drivers. New technologies have been developed to identify those AF drivers and are used as a guide for catheter ablation. This review article aims to provide a comprehensive overview of the current state of knowledge regarding AF drivers and the various mapping approaches used to identify them.